The Soviet Union, Eastern Europe, and the Third World - Kanet, Roger E. 1936- (Cambridge University Press, 1987)
Soviet policy towards the countries of Asia, Africa and Latin America has undergone substantial expansion and change during the three decades since Khrushchev first initiated efforts to break out of the international isolation in which the USSR still found itself in the immediate post-Stalin years. Over the course of the past thrity years the Soviet Union has expanded significantly both the geographical range of its involvement with developing countries, and the intensity of its political, military and economic activities. Moreover the USSR has increasingly acted in consort with 'allies' such as Cuba and the countries of Eastern Europe. The studies in this volume, first published in 1988, examine various aspects of Soviet and East European policy towards the Third World